Pond Eutrophication - Burden, Maxwell; Guo, Quanqing; Krueger, Laura; Young, Nicholas (Kansas State University. K-State Libraries, 2018)
Landowners Bruce and Theresa Meyer of Palmer, KS, requested a design to address eutrophication issues causing blue-green algae blooms within their pond. The blooms impact recreational activities such as swimming, fishing, and canoeing. Currently, their solution is temporary and requires the use of chemicals to harden the water and remove the algae. The Meyer’s have requested a more permanent and cost-effective solution. After completing the engineering design process, two design options are proposed for reducing the effects of eutrophication: vegetative buffer strips and a floating garden. Vegetative buffer strips are used to filter nutrients and sediment from runoff, which will reduce the growth of the blue-green algae. A floating garden has the potential to provide an in-pond solution to reduce excess nutrients, but requires more maintenance and recurring costs. Well-planned buffer strips have a higher chance of providing a long-term solution compared to the floating garden, which would have to be maintained and reinstalled yearly. The final proposed design uses both designs in tandem to synergistically reduce the effects of eutrophication. Water inflow will be rerouted through the vegetative filter through present vegetation, which will reduce the amount of incoming nonpoint source pollutants that enter the pond. The floating garden will be utilized to reduce excess nutrients that are within the pond.
Citation: Burden, M., Guo, Q., Krueger, L., & Young, N. (2018) Pond Eutrophication. Unpublished manuscript, Kansas State University, Manhattan, KS.
Kirmser Undergraduate Research Award - Group Category, grand prize